The Use of Next-Generation Sequencing in the Identification of a Fastidious Pathogen: A Lesson From a Clinical Setup. (30th January 2017) - Saeb, Amr TM; Abouelhoda, Mohamed; Selvaraju, Manojkumar; Althawadi, Sahar I; Mutabagani, Maysoon; Adil, Mohammad; Al Hokail, Abdullah; Tayeb, Hamsa T
Clostridium haemolyticum is the causal agent of bacillary hemoglobinuria in cattle, goat, sheep, and ruminants. In this study, we report the first recorded human-infecting C. haemolyticum strain collected from an 18-year-old woman diagnosed with acute lymphoblastic leukemia. After failure of traditional techniques, only next-generation sequencing (NGS) technology in combination with bioinformatics, phylogenetic, and pathogenomics analyses revealed that our King Faisal Specialist Hospital and Research Center (KFSHRC) bacterial isolate belongs to C. haemolyticum species. KFSHRC isolate is composed of 1 chromosome and 4 plasmids. The total genome size is estimated to be 2.7 Mbp with a low GC content of 28.02%. Comparative pathogenomics analysis showed that C. haemolyticum KFSHRC isolate is a potential virulent pathogenic bacterium as it possesses the virulence factors necessary to establish an infection, acquire essential nutrients, resist antimicrobial agents, and tolerate hostile conditions both in the human host and in its surrounding environment. These factors are included in the main chromosome in addition to novel recombination of the plasmids, and they could be the reason for the incidence of that human infection. This work demonstrated the importance of using NGS in medical microbiology for pathogen identification. It also demonstrates the importance of sequencing more microbial samples and sharing this information in public databases to facilitate the identification of pathogenic microbes with better accuracy.